Estudo de concordância entre médico e não-médico em protocolo ecocardiográfico simplificado para detecção da insuficiência cardíaca - Wandeir Wagner de Oliveira (2018)
Introduction: Cardiovascular diseases (CVD) are the main causes of death in the Brazilian population. Heart failure (HF) is the main endpoint of CVDs with a high morbidity and mortality rate. Therefore the precise diagnosis with the early identification of the etiological cause allows effective therapeutic interventions improving the survival and quality of life of the patients. For a precise diagnosis of HF the examination of choice is transthoracic echocardiography (TTE) but it is not always achieved in a timely manner due to the sustainability difficulties of the brazilian health system (SUS). Thus the use of a tele-echocardiogram may be useful to improve patients access to echocardiographic evaluation in places where there is a shortage of trained physicians. Objective: To analyze the reliability of a simplified echocardiographic screening protocol for HF when the imaging is performed by a non-medical professional and by an experienced echocardiographer at a distance. Methods: 174 patients underwent TTE by an echocardiographer on site. A moving image protocol (MPEG format, 3 cycles for each image) was stored: parasternal long axis, apical four chambers with and without color Doppler. Soon after, a nurse with 20 hours of training in TEE, without knowledge of the result, acquired the same protocol. The exams were randomized and sent to a remote observer, another expert physician echocardiographer, masked in relation to who had collected the protocol. He gave a qualitative visual perception to the study variables (presence, absence, can not evaluate): LV systolic dysfunction, LV hypertrophy, LV dimensions, RV dysfunction and / or increase, AE increase, mitral and / or aortic valvulopathy. The reliability of the images was evaluated by Kappa agreement. Results: The group studied was 108 women (62.1%) and 66 men (37.9%) with mean age of 58.5 ± 16.6 years. It was observed that the agreement obtained by the remote echocardiographer when analyzing the images of the nurse versus images of the was considered almost perfect for LV increase (k = 0.84), left ventricular hypertrophy (k = 0.84), LV systolic dysfunction (k = 0.82) and increase in AE (k = 0.80). For the RV increase the agreement was considered substantial (k = 0.72). Concerning mitralaortic valve disease, agreement was moderate (k = 0.56). Conclusion: The results demonstrate that, in the protocol studied, there was a good agreement between the images performed by a nurse or an echo expert when it were analyzed at a distance by another expert.